2022
DOI: 10.3390/plants11233207
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Genes Involved in Fatty Acid and Lipid Biosynthesis in Developing Walnut (Juglans regia L.) Seed Kernels from Qinghai Plateau

Abstract: Walnut (Juglans regia) is an important woody oil-bearing plant with high nutritional value. For better understanding of the underlying molecular mechanisms of its oil accumulation in the Qinghai Plateau, in this study we monitored walnut fruit development, and 15 cDNA libraries were constructed from walnut seed kernels collected at 72, 79, 93, 118 and 135 days after flowering (DAF). The candidate genes were identified using sequencing and expression analysis. The results showed that the oil content in the kern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Endopleura color is a vital factor for determining the economic value and aesthetic appeal of nuts and in crop breeding. Very little systematic analyses of endopleura color have been carried out in woody crops [ 19 , 26 ]. Walnuts ( Juglans ) are a key ebible nut that are high in proteins, amino acids, lipids, and carbohydrates, as well as a variety of trace elements and minerals [ 20 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endopleura color is a vital factor for determining the economic value and aesthetic appeal of nuts and in crop breeding. Very little systematic analyses of endopleura color have been carried out in woody crops [ 19 , 26 ]. Walnuts ( Juglans ) are a key ebible nut that are high in proteins, amino acids, lipids, and carbohydrates, as well as a variety of trace elements and minerals [ 20 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Walnuts are a typical food that can be used as a medicine as well as food; it is a medicine listed in the Chinese Pharmacopoeia [ 21 25 ]. Its medicinal efficacy is mostly related to the rich polyphenol and flavonoid components, which have antioxidant and immunity-enhancing effects, and has been a hotspot for research and development in recent years [ 26 28 ]. The walnut kernel consists of the embryo (seed kernel or kernel) and the endopleura (seed coat, kernel membrane), the walnut endopleura is wrapped in a layer of film on the surface of the kernel [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of vegetable oil mainly involves the synthesis of fatty acids in the plastids and the synthesis of TAGs in the endoplasmic reticulum. Shi et al [ 8 ] have shown that there were five kinds of main fatty acids in the mature walnut seeds: palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1), linoleic acid (18:2), and linolenic acid (18:3). During the period of oil rapid accumulation, the content of saturated fatty acids decreased rapidly, while the content of unsaturated fatty acids increased rapidly [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 28 genes related to walnut oil biosynthesis were screened out, corresponding to 17 differential expression miRNAs. Huang et al [ 23 ] and Shi et al [ 8 ] have sequenced transcriptomes during walnut seed kernel development, which increases the available transcriptome data for walnut seed kernels’ lipid metabolism. Recently, walnut genome assembly at the chromosome level was published, which will be more conducive to walnut transcriptome research [ 24 ].…”
Section: Introductionmentioning
confidence: 99%